Three-dimensional ultrasonographic evaluation of carotid artery plaque surface irregularity - Artas, Hakan; Okcesiz, Izzet (Termedia Publishing House Ltd, 2020)
Introduction: The aim of this study was to evaluate 3-dimensional (3D) ultrasonography (US) in determining the surface irregularity of carotid artery plaques. Material and methods: This study included 50 patients (20 females and 30 males) aged between 56 and 82 years with plaques in the carotid artery which were detected during routine neck ultrasound. Simultaneously these cases were evaluated in terms of plaque echogenicities and surface characteristics with 2D and 3D US. Results: 3D imaging was successfully performed in 45 of the 50 cases and the technical success rate was 90%. A single plaque was detected in 64.4% of the patients, with the remaining 35.6% having more than one plaque. The lengths of the plaques ranged from 2 to 12 mm (mean: 3.98 +/- 1.70 mm); the widths ranged from 1.8 to 3.2 mm (mean: 2.11 +/- 0.37 mm). No significant difference was found between 2D and 3D plaque echo-structures (observer 1, p = 0.317; observer 2, p = 0.276), but there were significant differences between 2D and 3D plaque surface irregularities (observer 1, p = 0.002; observer 2, p = 0.004). The inter-observer agreement on 2D and 3D plaque echo-structure and surface irregularity was very good (k coefficients were 0.89 and 0.83, respectively, for echo-structure, and 0.91 and 0.95, respectively, for surface irregularity). Conclusions: The present study shows that 3D US examination is a valuable non- invasive method for investigation of surface irregularity of carotid artery plaques.
Keywords: carotid plaque; 3D ultrasonography; surface irregularity